Single injection paravertebral block for renal surgery in children - Berta, Emil; Špaňhel, Jiří; Šmakal, Oldřich; Smolka, Vratislav; Gabrhelík, Tomáš; Lonnqvist, Per-Arne (Paediatric anaesthesia, 2008)
BACKGROUND: Continuous paravertebral block (PVB) has been successfully used for postoperative analgesia in children. However, data regarding the efficacy of a single injection technique for major renal surgery are still lacking. METHODS: Following the ethics committee approval and parent informed consent, 24 children (median 10.3 months; range: 2.9-26.8) undergoing major renal surgery were included in a prospective observational pilot study. Following a standardized general anesthetic the patients were administered a single injection low thoracic PVB (loss-of-resistance technique; 0.5 ml.kg(-1) of levobupivacaine 2.5 mg.ml(-1) with epinephrine 5 mug.ml(-1)) at the end of surgery. Postoperative pain was assessed by Face, Legs, Activity, Cry, Consolability (FLACC) score at predetermined time points and in case of apparent patients' discomfort during the first 12 postoperative hours. The duration of postoperative analgesia was defined as the interval between PVB and the first supplemental administration of a rescue opioid analgesic. The incidence of complications and postoperative vomiting (POV) was also recorded. RESULTS: A successful PVB was achieved in 23/24 patients (95.8%). The median duration of the block was 600 min (range: 180-720 min) with 10 children not requiring any supplemental analgesia during the 12-h observation period. Vascular puncture was observed in 2/24 children (8.3%) and POV occurred in 4/24 children (16.7%). All complications were considered minor and did not influence recovery. CONCLUSIONS: Single injection PVB provided clinically relevant postoperative analgesia in children undergoing major renal surgery.
Keywords: výsledek terapie; Male; Child, Preschool; Nerve Block; Thoracic Vertebrae; pooperační bolest; Infant; agonisté adrenergních receptorů; pilotní projekty; Injections, Spinal; Analgesics, Opioid; měření bolesti; Kidney; Prospective Studies; mužské pohlaví; opioidní analgetika; hrudní obratle; spinální injekce; anestetika lokální; adrenalin; Adrenergic Agonists; Treatment Outcome; Bupivacaine; Time Factors; předškolní dítě; Epinephrine; lidé; Anesthetics, Local; ženské pohlaví; Humans; ledviny; nervová blokáda; bupivakain; kojenec; časové faktory; Pain, Postoperative; Pilot Projects; Female; Pain Measurement; prospektivní studie